Safety and tolerability of a novel oral nutritional supplement in healthy volunteers. Issue 3 (March 2021) - Bonelli, Annalisa; Menna, Pierantonio; Minotti, Giorgio; Angeletti, Silvia; Comandini, Alessandro; Picollo, Rossella; Quarchioni, Elisa; Russo, Vincenzo; Salvatori, Enrica; Ferravante, Francesca; Emerenziani, Sara; Cicala, Michele; et al.
Summary: Background and objective: Foods for Special Medical Purposes (FSMPs) are formulated to support the nutritional needs of subjects with impaired capacity to ingest, digest or absorb ordinary food or nutrients. Polglumyt® is a proprietary highly purified, high quality glycogen obtained from mussels. Here we report the results of a single-center, single dose, open label, single arm study carried out to investigate acceptance (i.e. gastrointestinal tolerance and palatability), metabolic profile and safety of a low osmolarity, high-density energy Polglumyt®-based drink (the investigational product, IP) as a novel FSMP. Methods: Twelve healthy subjects received a single oral administration of the IP under fasting conditions. The study endpoints were: changes in gastrointestinal system tolerability at 3 h, 6 h and 24 h after IP intake; IP palatability evaluation; metabolic evaluation through the kinetic profile of circulating glucose, insulin and C-peptide from 0 h to 6 h after IP intake and changes from baseline in circulating triglycerides at 3 h and 6 h after IP intake. Results: The IP showed a good gastrointestinal tolerability and an acceptable palatability. The IP did not affect the physiological glycemic profile and the triglycerides levels 6 h after the intake. The IP was well tolerated by study subjects, with no or minor adverse events. Conclusions: The study results encourage additional clinical investigations on the IP as a novel FSMP in patients with impaired digestion or gastrointestinal absorption, unable to assume an ordinary diet, e.g. patients undergoing invasive gastrointestinal surgery, elderly or oncological patients, even with certain metabolic disorders.